Digital Curriculum Facing Technological Challenges in Education - Dina Rahmadani S. Manopo; Nur Amelia Arsyad; Imelda; Sri Ade Putri Mahadjani; Sabrian Suwel; Syukria Sukma Pakaya; Fikran Diange; Rizkianto Giasi; Nur Walida S. Tuna; Marsellad.Gui (International Journal of Advanced Technology and Social Sciences, 2023)
This research explores the challenges and opportunities associated with digital curriculum in the face of technology in learning context of the digital age in Indonesia. Using a mixed methods approach, the research combines qualitative and quantitative data from educators, policymakers, students and parents to gain comprehensive insights. The findings reveal the current state of technology integration, highlighting gaps in technology access and infrastructure. Addressing the digital divide and providing appropriate professional development for educators were identified as critical steps to unlocking the full potential of technology to improve education in Indonesia. Localization of digital content and the creation of inclusive, technology-driven learning environments are critical to preparing students for an increasingly technology-centric future